Validation of UV coiled tube reactor for fresh juices. Issue 3 (1st May 2007) - Patazca, Eduardo; Koutchma, Tatiana; Parisi, Brian
Abstract : The objective of this study was to validate the performance of a coiled ultraviolet (UV) module with 24 lamps for fresh juice pasteurization. Escherichia coli K12 at an inoculation level of 10 6 cfu mL -1 was chosen as a target microorganism for biodosimetry. All tested fruit juices highly absorbed UV light, with absorption coefficients ranging from 11 cm -1 to 78 cm -1 for lillikoi and pineapple juice, respectively. Of the juices examined, pineapple juice appeared to be the worst case scenario in terms of UV absorptivity and high viscosity. A caramel model solution was developed to mimic juice absorption properties and was used for inoculation studies. The 5-log10 reduction standard under turbulent flow required by the FDA was achievable in Newtonian liquids with absorption coefficient less than 15 cm -1 after one pass. Turbulent flow was not developed in more viscous orange and pineapple juices at the flow rates tested. A biodosimetry technique that utilizes E. coli as a tracer showed no distribution of UV dose in liquids with absorption coefficient lower than 26 cm -1 . The proposed technique may assist in validating the performance of UV reactors and improve efficiency of UV pasteurization.